Social relations in compulsory schools in Iceland and their relationship to student achievement and teaching practices - Björnsdóttir, Amalía; Hansen, Börkur (Menntavísindasvið Háskóla Íslands, 2018)
The literature on school leadership and management emphasizes the importance of good relations between school leaders, teachers, parents, and students (Harris, 2008, 2014; Hoy & Hoy, 2009; Kaplan & Owings, 2015; Sergiovanni, 2006, 2009).Sergiovanni (2006) states that the major difference between old and new management theories can be manifested in their respective emphases on “power over” and “power to.” He states that the major emphasis of traditional theories was to seek “reliability and predictability by increasing control over events and over people,” whereas new theories seek predictability by “controlling probabilities” through shared goals and purposes (pp. 96–97). His thesis is that schools need to be developed as moral communities with proactive and reflective cultures concerning teaching and learning.According to Hargreaves and Fullan (2012), the term “professional capital” is composed of three sub-elements: human, social, and decisional (human capital refers to the knowledge and skills involved in teaching and learning, social capital to the quality of interactions and relationships in schools, and decisional capital to discretionary judgments and decisions in practice). The level of social capital can, accordingly, be seen as demonstrating different relationship settings in schools and “powers to” collaborate and achieve desired ends.Different relationship settings in schools suggest differences in capital and “powers to” collaborate and achieve desired ends.Social relations and academic achievement have been researched quite extensively since the Coleman study in 1966. Most of those studies have focused on the relationship of students’ social background to achievement, but others have focused on the link between school characteristics and achievement. Generally, these studies show a positive relationship between good relations within schools and the academic attainment of students (Acar, 2011).It is, therefore, of interest to explore, in an Icelandic context, the connection between social ...